If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 28 = f + -3 Reorder the terms: 28 = -3 + f Solving 28 = -3 + f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-1f' to each side of the equation. 28 + -1f = -3 + f + -1f Combine like terms: f + -1f = 0 28 + -1f = -3 + 0 28 + -1f = -3 Add '-28' to each side of the equation. 28 + -28 + -1f = -3 + -28 Combine like terms: 28 + -28 = 0 0 + -1f = -3 + -28 -1f = -3 + -28 Combine like terms: -3 + -28 = -31 -1f = -31 Divide each side by '-1'. f = 31 Simplifying f = 31
| 6000=4 | | 6(p-8)=-42 | | -30+(150)=X | | 24=2(-x+3) | | 2(3y+4+2)= | | 17+10x-3=-3(x-6) | | 14x+8+10x+28=180 | | 9x+5=12x-19 | | 6-(-7+x)=42 | | 600=2x+3y | | -6(5n+5)=-120 | | 8x-27=4x+33 | | 140=90+m | | 12-4x=-5x+22 | | 12x^2+26x-10=0 | | 2(g+4)+5g-1= | | 3n+28=200 | | 0.75n+1.29=7.00 | | x(2x-5)(x^2-3)(5x^3-8)=0 | | -3x=-5x+22 | | 5x-31=2x+5 | | 7x-36=4x+5 | | 5y-[2(y+1)+2]=7z | | (4.6-8n)0.5=3.8 | | 4n-25=75 | | 2(4-x)+7x=13 | | 4x+4=7x-17 | | x+5.5y=x+y+81 | | 4(5a+16)=16(a-35) | | 3x^4-13x^2=10 | | 32n+120=720 | | 6x-29+2x+24=67 |